Inguinal hernia repair under local anaesthesia - Mhawes, Ali Abed; Badrideen, .Badrideen Lauy; Huoeil, .Basheer Abdali (AL-Kindy College Medical Journal, 2015)
Background: For various reasons, inguinal hernia repair under local anaesthesia is not well accepted to both patients and surgeons. The patients fear from pain and surgeons need full relaxation and co-operation to do successful hernia repairMethods: purpose of this study is to evaluate the effectiveness of local anaesthesia in inguinal hernia repair.prospective study was made from January 2011-0ctober 2013 , on a total of 50 patients with inguinal hernia operated on under local anaesthesia. Patients were selected primarily on the basis of their willingness to accept the procedure after the technique was described to them.Results: In this study 50 patient and 58 herniorrhaphies done for them during a period of about 34months were evaluated .A questionnaire was sent to each patient postoperatively to aid in evaluating the subjective reactionto the local anaesthesia. all patients were males ,age range between 31-83 year, median age 51 .types of inguinal hernia were sliding 1case ,pantaloon 5cases ,indirect 28cases ,direct 24 cases ,Rt. Side 27cases, Lt. side 15 cases ,bilateral hernia 8 cases .we give local anesthesia by 2 methodsConclusions: Local anesthesia is without question the safest available technique of anesthesia.Local anesthesia is an extension of the surgical procedure (indeed, often an integral part of that procedure), and as such its administration should be the concern of the surgeon